(3GdeMGSf GdeLJeYI hGdCfhGQ GdedJeYI aj aVGFd GdNdaGA GdGQHYIs - (3YHO GdQMef Hf YHO GdSdGe GdUahQj GdTGaYjs ((3SdjeGf Hf Cejf Hf YHO GdQMef GdCjhHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CJbf eG GUWfYg s
(3Cdag SfI (B884(3g`s
(3QJHI Ydi CQHYI CHhGHs
(3hNJeI HeQHYI YHO Gddg Hf YHGS QVi Gddg YfgeG NUGd GdfHi Udi Gddg Ydjg hSde heOMIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs